Mitigating ethnic disparities in covid-19 and beyond - Razai, Mohammad S; Kankam, Hadyn K N; Majeed, Azeem; Esmail, Aneez; Williams, David R (BMJ (Online), 2021)
Although socioeconomic status partly explains ethnic disparities seen with covid-19, cultural and structural racism also adversely affect health, argue Mohammad Razai and colleagues